Global Compensation - Soetjipto, Budi W. (Forum Manajemen; Vol 12 No 66 (1998): Forum Manajemen Prasetiya Mulya | Back to Basics, 1998)
Available survey data indicate a rapid increase in the number of companies adopting this method (O'Neill & Lander, 1993/1994). I believe the main reason behind that is because adopting skill-based method can encourage every individual in the company· to have new, desired competencies, and having competent employees is one important factor for the company being success in global competition.